The new zinc(II) phthalocyanine directly conjugated with 4-butylmorpholine units: Synthesis, characterization, thermal, spectroscopic and photophysical properties - Mutlu, Fatih; Piskin, Mehmet; Canpolat, Erdal; OztUrk, Omer Faruk (Elsevier, 2020)
In this study, new peripheral tetra-4-butylmorpholine substituted zinc(II) phthalocyanine was synthesized through C-C bond formation using the palladium catalyzed Suzuki-Miyaura coupling reaction. Its structure was characterized by elemental analysis, FT-IR, H-1 NMR, C-13 NMR, UV-vis, fluorescence, and MALDI-TOF-mass spectroscopic techniques. Its thermal property were evaluated by thermogravimetric analysis and differential scanning calorimetry. In addition, the photophysical properties of the zinc(II) phthalocyanine were also investigated in DMSO. (C) 2019 Published by Elsevier B.V.
Keywords: Phthalocyanine; 4-Butylmorpholine; Suzuki-miyaura coupling reaction; Spectroscopic; Photophysical